Taking Charge of Systemic Sclerosis: A Pilot Study to Assess the Effectiveness of an Internet Self‐Management Program. Issue 5 (May 2014) - Poole, Janet L.; Mendelson, Cindy; Skipper, Betty; Khanna, Dinesh
<x xml:space="preserve">Abstract</x> Objective To assess the effects of an internet self‐management program for systemic sclerosis on self‐efficacy, health efficacy, and management of care, pain, fatigue, functional ability, and depression. Methods Participants logged on to a password‐protected web site and completed modules and learning activities at their own pace over 10 weeks. Participants were encouraged to log on to the discussion board, participate in an interactive component of the web site, and respond to questions posted for each module. Participants completed pre‐ and postintervention questionnaires on perceived self‐efficacy, health efficacy, ability to manage care, functional disability, depression, pain, and fatigue. They also completed an 8‐question evaluation form regarding satisfaction with the web site, program content, discussion boards, and learning activities. Results Sixteen participants completed the study and postintervention measures. There were significant improvements in mean scores for ability to manage care (effect size [ES] 0.62, P = 0.025) and health efficacy (ES 0.72, P = 0.012), and significant decreases in fatigue (ES −0.55, P = 0.045) and depression (ES −0.71, P = 0.013). Self‐efficacy improved, but not significantly. The evaluation of the program revealed mean scores ranging from 4.2 (web site was visually appealing) to 4.9 (information presented clearly) on a 5‐point scale, where 5 is most satisfied. Conclusion These findings from this pilot study suggest that a self‐management program delivered using an internet format can lead to statistically significant changes in health efficacy and management of care, fatigue, and depression. These results need to be confirmed with a larger randomized controlled trial with a longer followup period.